The early definitive internal fixation of Complex Pelvic Fracture and its outcome: our experience in level 1 trauma care centre. - Kimmatkar, Nitin; H., Kantharaju (International Journal of Research in Orthopaedics, 2022)
Background: Complex pelvic fractures have high mortality and morbidity hence required urgent resuscitation, haemodynamic stabilization and fracture fixation. Keeping in mind the various schools of thought regarding definitive management, there is need to study the outcomes of complex pelvic fractures after internal fixation surgery. Methods: Twenty patients with complex pelvic fractures treated with internal fixation surgery in between 1st June 2018-31st December 2019 with at least 12 months follow-up were included. Clinical and functional outcome of these patients was studied and evaluated using Majeed and Hannover scoring systems. Results: Of 20 patients, 19 had closed while 1 had open pelvic fracture while 11 had tile type B and 9 had tile type C fracture. After 12 months of follow up, 72% patients of tile B fractures and 55.6% in tile C had excellent Majeed score with rest having good score. Hannover score was very good in 36.4% tile B cases and 22.2% tile C cases and good in 63.6% tile B cases and 77.8% tile C cases. Type of fracture (type B or type C) had a statistically significant co-relation with chronic pain (p=0.016). It was also found that urogenital injury and sexual dysfunction (p=0.007) had a significant co-relation. Conclusions: Early definitive internal fixation in patients with complex pelvic fracture had very good clinical and functional outcome. Most common associated injuries in complex pelvic fractures are urogenital injuries due to close proximity. In the outcomes chronic pain and sexual dysfunction are major issues. The sexual dysfunction patients usually associated fracture of pubic rami or pubic diastasis.